Innovative SMEs: the role of intellectual capital and board size in shaping financial performance - Gotti, Giacomo; Morrone, Carla; Ferri, Salvatore; Komilova, Khurshida (Piccola Impresa / Small Business, 2025)
Purpose. Nowadays, intellectual capital (IC) is a crucial driver of value creation, particularly for innovative firms. This study investigates the relationship between IC efficiency and firm performance (FP), with Board of Directors (BoD) size acting as a moderating variable. Although, BoD size-FP relation has been extensively explored in the literature, findings remain inconsistent. Resource-based view suggests that larger BoDs offer diverse experiences, perspectives and knowledge, enhancing decision-making; conversely, agency theory suggests that larger BoDs may lead to higher communication and coordination costs. Design/methodology/approach. Using ordinary least squares (OLS) regression, we analyze data from 2,166 Italian innovative small and medium-sized enterprises (ISMEs). We test the relationship between IC (proxied by value-added intellectual coefficient (VAIC)) and FP (proxied by return on assets and return on equity), considering the moderation role of BoD size. We also employ Lasso regression for robustness. Findings. IC efficiency significantly and positively impacts FP, with BoD size playing a significant moderating role. These findings are robust across both OLS and Lasso regressions. Practical and social implications. The findings are relevant for both managerial practice and scholars. They contribute to resource-based and agency theories by offering insightful outcomes on a novel sample. Furthermore, these results can also inform corporate governance practices in innovative SMEs regarding IC orchestration.